Assessing the economic impact of obesity and overweight on employers: identifying opportunities to improve work force health and well-being - Timothy M. Dall; Tanvi Sapra; Zachary Natale; Tia Livingston; Fang Chen (Nutrition & Diabetes)
Abstract Background and objectives Obesity is a major public health issue, significantly affecting national and individual health and economic well-being. This study quantifies the economic impact of excess body weight on employers and employees in 2023, offering insights for obesity prevention and treatment. Methods We utilized data from the National Health Interview Survey, National Health and Nutrition Examination Survey, Medical Expenditure Panel Survey, and Current Population Survey. Published reports and original estimates were combined to assess the economic burden for the U.S. and across seven major industries (Construction, Education & Health, Financial Activities, Government, Manufacturing, Professional & Business Services, and Transportation & Utilities). We compared the economic outcomes for adults with obesity and overweight to those with healthy weight, focusing on direct and indirect costs. Potential savings from different weight loss scenarios were estimated using the Disease Prevention & Treatment Microsimulation Model. Results In 2023, among 158 million civilian employees on nonfarm payrolls, 30% had obesity and 34% had overweight, resulting in a combined economic burden of $425.5 billion (obesity: $347.5 billion; overweight: $78 billion). This includes excess medical costs of obesity ($115 billion), presenteeism (obesity: $113.8 billion; overweight: $46.5 billion), absenteeism from obesity ($82.3 billion), excess medical costs of overweight ($31.5 billion), obesity-related disability payments ($31.1 billion), and workers’ compensation payments ($5.2 billion). For a hypothetical firm with 10,000 employees (plus dependents), the annual costs were $22 million for obesity and $4.9 million for overweight, with average costs of $6472 per employee with obesity, $1244 per employee with overweight, $1514 per adult dependent with obesity, and $380 per adult dependent with overweight. Medical savings over 5 years range from $153.3 billion with a 5% weight loss to $326.1 billion with 25% weight loss at the industry level. Conclusion The substantial economic costs imposed by obesity and overweight on employers and employees highlight the need for resources dedicated to treatment and prevention, which can result in reduced medical expenses and improved productivity.